K Shell X-Ray Fluorescence Parameters of Some Elements in the Atomic Range 40 <= Z <= 50 - Önder, Pınar; Turşucu, Ahmet; Yılmaz, Demet (HINDAWI LTD, 2013)
The production cross sections sigma(Ki), the fluorescence yield W-K, K shell X-ray intensity ratio I-K beta/I-K alpha, the vacancy transfer probabilities from K to L shell eta(KL), and the Gamma(K) level widths for some elements in the atomic range 40 <= Z <= 50 were measured. The samples were excited by 80.998 keV gamma rays from a 10 mCi Ba-133 radioactive source. The K X-rays emitted by samples were detected by using a CdTe detector. These parameters have been theoretically calculated, also. The experimental values were compared with the theoretical and semiempirical values. Our experimental values closely agreed with theoretical values and other experimental values.
Keywords: VACANCY TRANSFER; PROBABILITIESAUGER; TRANSITION RATES; ALPHA INTENSITY RATIOS; CROSS-SECTIONS; YIELD; SWIDTHS; FE